Development of the disable software reporting system on the basis of the neural network - Gavrylenko, Svitlana; Babenko, O.; Ignatova, E. (My University, 2018)
The PE structure of malicious and secure software is analyzed, features are highlighted, binary sign vectors are obtained and used as inputs for training the neural network. A software model for detecting malware based on the ART-1 neural network was developed, optimal similarity coefficients were found, and testing was performed. The obtained research results showed the possibility of using the developed system of identifying malicious software in computer systems protection systems.
Keywords: PE-file structure; antivirus programs; computer systems; malicious software; signature method; heuristic method; ART-1 neural network